Activity-Based Systems Approach as a Framework for Methodology Programs in Forensic Science Research - Oleg A. Krestovnikov (Теория и практика судебной экспертизы, 2018)
The activity-based systems approach has been gaining in importance as a method of scientific inquiry, with its methodological orientation towards the study of objective reality in its relationship with our understanding of the nature, structure and genesis of various forms of activity. «Activity» is a central concept of this approach that reflects the multidimensional and multilayered nature of social existence. The scientific use of this concept has its roots in philosophical tradition. «Activity» is one of the more important categories in the system of forensic knowledge. Human activity is the key object of theoretical, applied and translational research in forensic science. This includes criminal activity as the object of inquiry, on the one hand, and forensic activity as the object of management and optimization, on the other hand.